Redox homeostasis in stomach medium by foods: The Postprandial Oxidative Stress Index (POSI) for balancing nutrition and human health - Kanner, Joseph; Selhub, Jacob; Shpaizer, Adi; Rabkin, Boris; Shacham, Inbal; Tirosh, Oren (Redox biology, 2017)
Red-meat lipid peroxidation in the stomach results in postprandial oxidative stress (POS) which is characterized by the generation of a variety of reactive cytotoxic aldehydes including malondialdehyde (MDA). MDA is absorbed in the blood system reacts with cell proteins to form adducts resulting in advanced lipid peroxidation end products (ALEs), producing dysfunctional proteins and cellular responses. The pathological consequences of ALEs tissue damage include inflammation and increased risk for many chronic diseases that are associated with a Western-type diet. In earlier studies we used the simulated gastric fluid (SGF) condition to show that the in vitro generation of MDA from red meat closely resembles that in human blood after consumption the same amount of meat. In vivo and in vitro MDA generations were similarly suppressed by polyphenol-rich beverages (red wine and coffee) consumed with the meal. The present study uses the in vitro SGF to assess the capacity of more than 50 foods of plant origin to suppress red meat peroxidation and formation of MDA. The results were calculated as reducing POS index (rPOSI) which represents the capacity in percent of 100g of the food used to inhibit lipid peroxidation of 200g red-meat a POSI enhancer (ePOSI). The index permitted to extrapolate the need of rPOSI from a food alone or in ensemble such Greek salad, to neutralize an ePOSI in stomach medium, (ePOS-rPOSI=0). The correlation between the rPOSI and polyphenols in the tested foods was R =0.75. The Index was validated by comparison of the predicted rPOSI for a portion of Greek salad or red-wine to real inhibition of POS enhancers. The POS Index permit to better balancing nutrition for human health.